RegB Kinase Activity Is Controlled in Part by Monitoring the Ratio of Oxidized to Reduced Ubiquinones in the Ubiquinone Pool - Jiang Wu (American Society for Microbiology, 2010)
ABSTRACT RegB is a membrane-spanning sensor kinase responsible for redox regulation of a wide variety of metabolic processes in numerous proteobacterial species. Here we show that full-length RegB purified from Escherichia coli membranes contains bound ubiquinone. Four conserved residues in the membrane-spanning domain of RegB are shown to have important roles in ubiquinone binding in vitro and redox sensing in vivo. Isothermal titration calorimetry measurements, coupled with kinase assays under oxidizing and reducing conditions, indicate that RegB weakly binds both oxidized ubiquinone and reduced ubiquinone (ubiquinol) with nearly equal affinity and that oxidized ubiquinone inhibits kinase activity without promoting a redox reaction. We propose a model in which ubiquinone/ubiquinol bound to RegB readily equilibrates with ubiquinones/ubiquinols in the membrane, allowing the kinase activity to be tuned by the redox state of the ubiquinone pool. This noncatalytic role of ubiquinone in controlling RegB activity is distinct from that of other known ubiquinone-binding proteins, which use ubiquinone as an electron donor or acceptor. IMPORTANCE Two-component signaling systems are comprised of a sensor kinase and a cognate response regulator that together control many cellular processes in response to a change in environmental conditions. Many sensor kinases are components of the cell membrane, with a domain that senses a specific environmental stimulus to control the activity of a cytosolic kinase domain. The broadly disseminated RegB/RegA two-component system regulates many energy-related processes in response to changes in the cellular redox state. In this study, the membrane-spanning sensor kinase RegB is shown to regulate its activity by interacting with the ubiquinone pool in a manner that involves novel noncatalytic equilibrium binding of ubiquinone.